Perkembangan Sistem Peradilan Pidana Di Indonesia - Gani Hamaminata (Pusat Riset dan Inovasi Nasional, 2023)
The Criminal Justice System outlined by the 1981 Criminal Procedure Code is an Integrated Criminal Justice System that is based on the principle of